Klippel-Feil syndrome and hearing loss - (:unkn) unknown (My University, 1996)
A wide variety of anomalies of the middle and inner ear has been reported in association with congenital deafness in Klippel-Feil syndrome. This syndrome is usually associated with sensorineural hearing loss. Conductive or mixed type hearing losses are rare. In this article this rare clinical entity and our case is discussed.
Keywords: Hearing loss; Klippel-Feil; Sensorineural